Development of Sharia Banking Intellectual Capital with A-IBVAIC - Neny Tri Indrianasari; Sochib Sochib; Riza Ramadhan (International Journal of Accounting and Management Research, 2023)
This study examines and analyzes the Intellectual Capital Development of Islamic Banking withA-IBVAIC. The variables used to test the model in this study are using VAICA-IBVAIC using three components namely HCE, INVCE, CEE. This research includes causality research. The population in this study were 24 BPRS in East Java Province.The data collection technique uses a documentation study by collecting secondary data, recording, and processing data related to this research. The data used includes: published bank financial reports from 2015 to 2021.Research results found thatIslamic Banking Value Added Human capitaleffect on profitability. This mattershows thatIslamic Banking Value Added Human capitalhas a positive relationship to ROA, if the value ofIslamic Banking Value Added Human capitalincreases, it will give an increase in ROA. Research results found thatIslamic Banking Value Added Innovation Capitalno effect on profitability. This proves thatcapital management innovation will generate more wealth for the owners of capital. Research results found thatIslamic Banking Value Added Capital employedno effect on profitability. This proves thatincrease or decrease fromscoreIslamic Banking Value Added Capital employednot following the increaseor a decrease in the company's ROA.